A compact, smart Langmuir Probe control module for MAST-Upgrade. (7th November 2017) - Lovell, J.; Stephen, R.; Bray, S.; Naylor, G.; Elmore, S.; Willett, H.; Peterka, M.; Dimitrova, M.; Havranek, A.; Hron, M.; Sharples, R.
Abstract: A new control module for the MAST-Upgrade Langmuir Probe system has been developed. It is based on a Xilinx Zynq FPGA, which allows for excellent configurability and ease of retrieving data. The module is capable of arbitrary bias voltage waveform generation, and digitises current and voltage readings from 16 probes. The probes are biased and measured one at a time in a time multiplexed fashion, with the multiplexing sequence completely configurable. In addition, simultaneous digitisation of the floating potential of all unbiased probes is possible. A suite of these modules, each coupled with a high voltage amplifier, enables biasing and digitisation of 640 Langmuir Probes in the MAST-Upgrade Super-X divertor. The system has been successfully tested on the York Linear Plasma Device and on the COMPASS tokamak. It will be installed on MAST-Upgrade ready for operations in 2018.